2006
DOI: 10.1002/ajmg.a.31409
|View full text |Cite
|
Sign up to set email alerts
|

Consanguineous marriage and congenital heart defects: A case‐control study in the neonatal period

Abstract: The original article to which this Erratum refers was published in Am J Med Genet Part A 140A:1524–1530.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Although a consistent positive association between consanguinity and disorders such as ventricular septal defect and atrial septal defect has been demonstrated, indicating the involvement of common variants, both positive and negative associations with patent ductus arteriosus, atrioventricular septal defect, pulmonary atresia, and tetralogy of Fallot have been reported in different populations (71)(72)(73)(74), suggestive of community-specific founder mutations. It is, however, also possible that nonstandardized diagnostic protocols may have contributed to the variant findings reported by different study centers.…”
Section: Consanguinity and Complex Diseasesmentioning
confidence: 99%
“…Although a consistent positive association between consanguinity and disorders such as ventricular septal defect and atrial septal defect has been demonstrated, indicating the involvement of common variants, both positive and negative associations with patent ductus arteriosus, atrioventricular septal defect, pulmonary atresia, and tetralogy of Fallot have been reported in different populations (71)(72)(73)(74), suggestive of community-specific founder mutations. It is, however, also possible that nonstandardized diagnostic protocols may have contributed to the variant findings reported by different study centers.…”
Section: Consanguinity and Complex Diseasesmentioning
confidence: 99%
“…Similarly our study also found M:F ratio 1.90 similar to the studies of Hussain [1] and Kumar [2] which was 2.08:1 and 1.78:1 respectively. In contrast, Khalid [3] and Khan [4] didn't find much of gender disparity. Gender discrepancy is quite striking, might be because of early reporting of male progeny by the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Khalid yunis, Reem SLRafel, 15 in 2008 stated in their article that most common form of consanguineous union was between first cousins i.e., third degree relationship.…”
Section: Citymentioning
confidence: 99%